INTERACTIVE LEARNING MEDIA DEVELOPMENT WITH CONCEPTUAL CHANGE FOR BASIC NURSING LECTURE I IN STIKES MAJAPAHIT SINGARAJA - Putu Yoga; Kadek Yudik Aryawan; Putu Adi Krisna Juniarta (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
Introduction: All this time conventional media in lecture proved less effective in improving learning outcomes Basic Nursing Science I. On the other hand, the presence of an innovative learning model of conceptual change-oriented and ICT are potentially improve learning outcomes IKD I. Development of interactive learning media-oriented conceptual change is predicted to have an impact on the achievement of learning outcomes IKD difference. This research aims to develop interactive learning media-laden conceptual change and test its effectiveness in scaling the learning outcomes of students STIKES Majapahit IKD Singaraja. Method: This was a development study (development research). The population in this study were all students of the first semester courses of S-1 Nursing, STIKES Majapahit Singaraja school year 2013/2014 (80 people) and a teacher of nursing staff (15 people). Sampling in each phase of the research done by simple random sampling technique, in order to obtain two lecturers (content and media experts), 3 students (individual test), 9 students (small group testing) and 30 students of the first semester (field test). The instrument used in this study is a questionnaire and achievement test I. Basic Nursing questionnaire used in the product development stage (testing expert, individual testing, small group testing), while the achievement test used during the field test. Criteria for success of media development is based on the evaluation of content expert, media experts, individual test, and test a small group. Also based on the analysis of the post-test scores of students, it can be seen the effective use of instructional media IKD I on student learning outcomes. Results: The results of the data analysis showed that the test class interactive learning media loaded developed conceptual change effective in optimizing learning outcomes IKD I (M = 80.08; SD = 5.93). Discussion: Through this research has successfully developed an interactive learning media charged to facilitate conceptual change classes first semester student IKD I STIKES Majapahit Singaraja. Besides, the validity of the analysis shows that interactive learning media charged velid developed conceptual change and unfit for use.Keywords: Conceptual change, interactive learning media charged conceptual change, and learning outcomes